Pengaruh Harga dan Kualitas Produk terhadap Keputusan Pembelian Konsumen di Toko Vani Fashion di jalan Gohor Lama Kabupaten Langkat Kecamatan Wampu - Cornelia Ivani; Tri Kartika Yudha; Tika Indria (Journal of Innovative and Creativity, 2025)
The research analysis aims to determine whether price influences consumer purchasing decisions at the Vani Fashion Store on Jalan Gohor Lama, Langkat Regency, Wampu District. Does product quality influence consumer purchasing decisions at the Vani Fashion Store on Jalan Gohor Lama, Langkat Regency, Wampu District. Do product price and quality influence consumer purchasing decisions at the Vani Fashion Store on Jalan Gohor Lama, Langkat Regency, Wampu District. This study uses multiple linear regression. The sample research was conducted using the "Accedential Sampling" method, which is a sampling method by choosing who happens to be there/met. In sampling, this study used the Zikmund formula so that the sample was 97 respondents. Primary data collection used a questionnaire. The results of the study showed that price partially had a positive and significant effect on consumer purchasing decisions at the Vani Fashion Store on Jalan Gohor Lama, Langkat Regency, Wampu District. Product quality partially had a positive and significant effect on consumer purchasing decisions at the Vani Fashion Store on Jalan Gohor Lama, Langkat Regency, Wampu District. Price and product quality simultaneously have a positive and significant effect on consumer purchasing decisions at the Vani Fashion Store on Jalan Gohor Lama, Langkat Regency, Wampu District.